A New Calibration for CORTAX: A computable general equilibrium model for simulating corporate tax reforms - Maria Teresa Alvarez Martinez; Salvador Barrios; Leon Bettendorf; Diego d'Andria; Maria Gesualdo; Simon Loretz; Dimitrios Pontikakis; Jonathan Pycroft (European Commission, Joint Research Centre (JRC), 2016)
The paper presents a new calibration for CORTAX (short for CORporate TAXation), which is a computable general equilibrium (CGE) model covering all EU member states, the US, Japan and a tax haven. The CORTAX model was originally built by the Centraal Planbureau (CPB) in the Netherlands based on the earlier OECDTAX model of Sorensen (2001). The calibration presented in this paper updates the base year to 2012. As the previous calibration was for 2007, the two calibrations represent pre- and post-crisis data. CORTAX models many key features of the corporate tax regimes including multinational profit shifting, investment decisions, loss compensation and the debt-equity choice of firms. The model is designed to investigate many aspects of corporate income taxation (CIT), including adjustment or harmonisation of the CIT rate or base and reforms to address the debt bias in CIT. Furthermore, it can examine consolidation of multinational CIT base, which inter alia addresses some of the issues concerning base erosion and profit shifting (BEPS). Given the choices companies have when confronted with changes in their respective environments, it is important to assess the effects of the reform under a general framework, which takes into account the interactions between different parts of internationally open economies, such as the impact of CIT reforms on firms' investment decisions. Indeed, as a computable general equilibrium model, it simulates all main macroeconomic variables, including GDP, investment and employment. The paper gives an explanation of the model structure, describes the data used, the calibration method and provides descriptive statistics for the baseline values of the model, comparing those for 2012 with the previous 2007 values.
Keywords: 330; Corporate taxation; Computable general equilibrium model; Model calibration; CORTAX